Detection and management of postpartum haemorrhage: Qualitative evidence on healthcare providers' knowledge and practices in Kenya, Nigeria, and South Africa - Akter, Shahinoor; Forbes, Gillian; Miller, Suellen; Galadanci, Hadiza; Qureshi, Zahida; Fawcus, Sue; Justus Hofmeyr, G.; Moran, Neil; Singata-Madliki, Mandisa; Amole, Taiwo Gboluwaga; Gwako, George; Osoti, Alfred; et al. (Frontiers in Global Women's Health, 2022)
Background Postpartum haemorrhage (PPH) is the leading cause of maternal death globally. Most PPH deaths can be avoided with timely detection and management; however, critical challenges persist. A multi-country cluster-randomised trial (E-MOTIVE) will introduce a clinical care bundle for early detection and first-response PPH management in hospital settings. This formative qualitative study aimed to explore healthcare providers' knowledge and practices of PPH detection and management after vaginal birth, to inform design and implementation of E-MOTIVE. Methods Between July 2020–June 2021, semi-structured qualitative interviews were conducted with 45 maternity healthcare providers (midwives, nurses, doctors, managers) of nine hospitals in Kenya, Nigeria, and South Africa. A thematic analysis approach was used. Results Four key themes were identified, which varied across contexts: in-service training on emergency obstetric care; limited knowledge about PPH; current approaches to PPH detection; and current PPH management and associated challenges. PPH was recognised as an emergency but understanding of PPH varied. Early PPH detection was limited by the subjective nature of visual estimation of blood loss. Lack of expertise on PPH detection and using visual estimation can result in delays in initiation of PPH management. Shortages of trained staff and essential resources, and late inter-hospital referrals were common barriers to PPH management. Conclusion There are critical needs to address context-specific barriers to early and timely detection and management of PPH in hospital settings. These findings will be used to develop evidence-informed implementation strategies, such as improved in-service training, and objective measurement of blood loss, which are key components of the E-MOTIVE trial (Trial registration: ClinicalTrials.gov: NCT04341662).